(3TQM aUjM KYdHs - (3eMeO Hf CMeO Hf gTGe Hf Nda GddNej GdCfOdSj, CHh YHO Gddg,J (B577 (3g` s; (3CHh GdYHGS CMeO Hf jMji Hf RjO KYdH GdTjHGfj Gdchaj GdfMhj,J (B291 (3g` s
(3ChdgG (B:s
(3SCdJfi habfi Gddg hGjGc defgLg Gdbhje hUQGWg GdeSJbje Cf CTQM dc eG hbY ai cJGH GdaUjM s
(3BNQgG (B:s
(3GdWQGQ eG JTHH Hg GdeQCI hLggG ajVai dhfg hjMSfg GfJgi GdTQM s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B252s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs